2009
DOI: 10.1029/2009jd011799
|View full text |Cite
|
Sign up to set email alerts
|

Testing E‐OBS European high‐resolution gridded data set of daily precipitation and surface temperature

Abstract: [1] Gridded data sets derived through interpolation of station data have a number of potential inaccuracies and errors. These errors can be introduced either by the propagation of errors in the station data into derived gridded data or by limitations in the ability of the interpolation method to estimate grid values from the underlying station network. Recently, Haylock et al. (2008) reported on the development of a new high-resolution gridded data set of daily climate over Europe (termed E-OBS). E-OBS is base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
315
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(332 citation statements)
references
References 32 publications
15
315
0
2
Order By: Relevance
“…A probability of exceedance of 0.001 corresponds to the 99.9th percentile precipitation could be considerably underestimated (by 15 to 51% in the grid boxes considered). Hofstra et al (2009) also found substantial differences between E-OBS and 3 other high-resolution data sets, in particular over topographically complex terrain such as the Alps. In agreement, we found differences between E-OBS and an alternative data set for the Rhine catchment area of approximately + 20%.…”
Section: Quality Of the Observations And Station Densitymentioning
confidence: 95%
See 2 more Smart Citations
“…A probability of exceedance of 0.001 corresponds to the 99.9th percentile precipitation could be considerably underestimated (by 15 to 51% in the grid boxes considered). Hofstra et al (2009) also found substantial differences between E-OBS and 3 other high-resolution data sets, in particular over topographically complex terrain such as the Alps. In agreement, we found differences between E-OBS and an alternative data set for the Rhine catchment area of approximately + 20%.…”
Section: Quality Of the Observations And Station Densitymentioning
confidence: 95%
“…This error mainly describes the error of the interpolation of the station observations to a very high resolution (0.1°base grid and the subsequent aggregation onto the 0.22°grid that is used here). In particular, the error related to spatial aggregation is difficult to assess because it is strongly dependent on estimates of the spatial correlation (shared variance), which is difficult to assess due to the low station density (see Hofstra et al 2009Hofstra et al , 2010. It is also not entirely clear whether this standard error should be interpreted as a random error or whether (in part) this error could be systematic.…”
Section: Sensitivity To Observation Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Frei and Schär, 1998, for an overview). A general dry bias, which can be exacerbated in mountainous terrain and for localised extremes, has been reported for E-OBS (Hofstra et al, 2009;Flaounas et al, 2012;Isotta et al, 2015).…”
Section: Observed Precipitationmentioning
confidence: 99%
“…E-OBS has been widely used for regional climate model evaluation (e.g. Lorenz and Jacob 2010;Nikulin et al 2011;Samuelsson et al 2011;Torma et al 2011;Flaounas et al 2013;Stéfanon et al 2014) and has been comprehensively evaluated in the literature (Hofstra et al 2009(Hofstra et al , 2010Kysel and Plavcov 2010;Flaounas et al 2012;Herrera et al 2012). In the E-OBS version 10 used here substantial improvements were realized, especially by increasing the station density (around 2000 for v1 and v2 vs. more than 4200 stations for temperature and more than 7300 for precipitation in v10).…”
Section: Observations: E-obs Datasetmentioning
confidence: 99%